Determinants of community participation in the development of sports tourism in the area of Sipin Lake Jambi City - Ugi Nugraha; Ely Yuliawan; Palmizal; Roli Mardian (Journal Sport Area, 2022)
Community involvement should be a major concern in the development of sports tourism because sustainability of tourism can be achieved through community participation. This study aims to analyze the level of community participation in the development of sports tourism and the factors that influence the level of community participation in the development of sports tourism in the Danau Sipin area of ​​Jambi City. The populations in this study are the people who live around the Sipin Lake tourist area, Jambi City. The sample in this study is selected using the quota sampling method, which is a technique of selecting samples to determine samples from the population that have certain characteristics until the desired number (quota) is 100 people. Researchers used a questionnaire to collect research data. Data analysis in this study includes descriptive data analysis and multiple regression analysis. The results of this study indicates that the level of community participation in the development of sports tourism is high. The results of this study also show that the economic impact, environmental impact, knowledge of the world of tourism, and entrepreneurial skills have a significant effect on community participation in the development of sports tourism, while social impacts and government support do not significantly affect community participation in the development of sports tourism. Simultaneously, the economic impact, social impact, environmental impact, knowledge of the world of tourism, government support, and entrepreneurial skills have a significant effect on the development of sports tourism. The Jambi City Government should increase the level of participation and knowledge of the community through socialization regarding the development of sports tourism in the Sipin Lake area and providing entrepreneurship skills training for the community around the area.